COMPLEX APPROACH TO TEACHING THE THEORETICAL MECHANICS USING THE INFORMATION AND COMMUNICATION TECHNOLOGIES - Ihor P. Boichuk; Olha I. Morozova; Tetiana V. Boichuk (Information technologies and learning tools, 2014)
Now special attention is given to improving the teaching methods of various subjects. It is connected with considerable development in information and communication technologies which surround us in everyday life. Now information systems and technology in the higher educational institutions are more often use during the educational process. In this paper complex approach to teaching the theoretical mechanics using the information and communication technologies in which students are provided with a spectrum of application of various technologies is proposed. Designed complex combines such components: training with the use of multimedia tools, lectures in electronic form, and knowledge control systems.